The characteristics and determinants of FDI in Ghana - Fabian Barthel; Matthias Busse; Robert Osei (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
Foreign Direct Investment (FDI) can be a valuable tool for development. However, not all forms of FDI are equally beneficial for the host country. The paper analyses the characteristics and determinants of FDI in a typical developing country: Ghana. Moreover, key policy areas are indicated, in order to enable Ghana both to attract more FDI and to increase the benefits from these capital inflows. The analysis combines qualitative and quantitative methods and is partly based on data retrieved from the World Bank's 2007 Enterprise Survey, and partly on our own survey of 54 multinational enterprises operating in Ghana.
Keywords: F21; F23; O55; 330; Foreign Direct Investment; Multinational Enterprises; Ghana